Scaling Up Rural Water Supply Service in Benin : A Programmatic Approach and Budget Support - Prevost, Christophe; Bea, Sylvestre; Leroy-Themeze, Claude (World Bank, Washington, DC, 2012)
People in rural areas of Benin have a greatly increased access to safe drinking water, thanks to government vision, donor support, and the investment and advisory assistance of the World Bank. In 2000, the government of Benin began preparing the ministries of key sectors for a shift from a project approach to a programmatic approach with enhanced budget support. The World Bank, through budget support operations and other donors, has supported Benin's reforms in budget preparation and management and in implementation of the country's poverty reduction strategy paper. The ministry of rural water supply was part of this move, and Benin is on track to meet the millennium development goals (MDG) target for its rural drinking-water supply. The smart lessons share how the World Bank contributed to Benin's remarkable progress in this sector.